2005
DOI: 10.1111/j.1468-2311.2005.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from ‘Near Misses’: Interviews with Women who Survived an Incident of Severe Self‐Harm in Prison

Abstract: This article describes qualitative research with women survivors of potentially lethal self-harm in prison. In-depth interviews were carried out during 2002/03 with 15 women, (adults and young offenders), from six establishments. The interviews focused on the women's own accounts of the 'near miss' incident, including intentions and motivations, factors leading up to the incident, experiences of care and support, current self-harm and suicidality, and suggestions for prevention. Recommendations include: improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 8 publications
4
61
0
Order By: Relevance
“…While this raises concerns about participants who are committed to carrying out a future suicide withholding information, evidence from prison studies suggests that in practice offenders welcomed the opportunity to disclose suicidal risk through the mediation of the interviewer, because they found it difficult to disclose directly to staff (Fazel, Hawton, Marzano & Rivlin, 2012). It is also helpful to provide the participant with the opportunity to choose if they would like anything to be passed onto a member of staff (Borrill et al, 2005). Developing trust and a non-judgmental approach are also both important issues when researching a sensitive subject such as suicide, particularly when using an offender population (Patenaude, 2004).…”
Section: Ethics and Difficulty In Obtaining Participantsmentioning
confidence: 94%
See 1 more Smart Citation
“…While this raises concerns about participants who are committed to carrying out a future suicide withholding information, evidence from prison studies suggests that in practice offenders welcomed the opportunity to disclose suicidal risk through the mediation of the interviewer, because they found it difficult to disclose directly to staff (Fazel, Hawton, Marzano & Rivlin, 2012). It is also helpful to provide the participant with the opportunity to choose if they would like anything to be passed onto a member of staff (Borrill et al, 2005). Developing trust and a non-judgmental approach are also both important issues when researching a sensitive subject such as suicide, particularly when using an offender population (Patenaude, 2004).…”
Section: Ethics and Difficulty In Obtaining Participantsmentioning
confidence: 94%
“…Despite this, past research has indicated that individuals who have experienced a near-lethal suicide incident and have taken part in research have not found it to be a negative experience, and in some cases found the experience to be beneficial (Fazel et al, 2012). Prison studies in which researchers interviewed inmates about suicide attempts found that listening was a key issue for staff-prisoner relationships, and that prisoners appreciated having someone to listen to them (Liebling & Price, 1999;Borrill et al, 2005).…”
Section: Ethics and Difficulty In Obtaining Participantsmentioning
confidence: 96%
“…Excluded from this definition are common expressive forms of body modification such as tattooing and piercing (Favazza, 1989). Attempted/completed suicides, although sometimes grouped with self-injury data in previous investigations, are viewed as distinct in etiology and motives and therefore deserving of separate investigation (Borrill et al, 2005; Canadian Centre on Substance Abuse, 2006).…”
Section: Manifestations and Motives For Sibmentioning
confidence: 99%
“…Replicating and expanding on earlier pilot work carried out by the Safer Custody Group, 36,37 this three-year project aims to explore some of the questions and risk factors that prison-based research has traditionally overlooked.…”
Section: Current Research On Near-lethal Self-harm In Prisonsmentioning
confidence: 98%
“…Although prisoner self-harm has been used as a proxy indicator for suicide, what may constitute a 'serious', 'severe' or 'near-lethal' incident has been variously and poorly defined, if at all. With a few notable exceptions, 36,37 it is questionable, and often difficult to establish, whether the prisoners involved in these studies may be considered to be ''virtual suicide victims". 38 Whilst it is important to avoid making artificial distinctions between different types and levels of self-harm, the study of such complex and dynamic behaviour(s) requires some clear and replicable criteria, which previous research has seldom included.…”
Section: Casementioning
confidence: 98%